Games as Information Systems - Xexéo, Geraldo; Mangeli, Eduardo; Silva, Farmy; Ouriques, Leandro; Costa, Luis Felipe Coimbra; Monclar, Rafael Studart (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
In this work, we formally build the construct of games as information systems. Starting from models and definitions that describe them, we present models that show game elements: components, players, environment, and their relations; as information systems elements. This paper also presents the analysis of five games and their elements based on that premise. As a ratification of our rationale, we present tools and visions shared by both fields. The presented premise and rationale could be easily linked to video games but, moreover, they are valid to all forms of games like tabletop games or sports.